Service Quality, Customer Attitude, and Satisfaction as Determinants of Patronage Intention in the Nepalese Banking Sector - Tamang, Aakriti; Balami, Surya; Lamsal, Damodar (Journal of Business and Social Sciences Research, 2025)
This study examines the effects of service quality, service attitude, and service satisfaction on patronage intention in Nepalese commercial banks. Using the cross-sectional research design, data were collected conveniently from 300 retail banking customers, and five direct structural paths were tested using CB-SEM. The findings show that service quality positively shapes customers’ service attitude and enhances their service satisfaction, consistent with service quality (SERVQUAL) and attitude formation theories which argue that customers’ evaluations of service performance influence their psychological responses. Service attitude was also found to significantly increase satisfaction. Furthermore, both service attitude and satisfaction emerged as strong predictors of patronage intention. By extending the SERVQUAL framework, this study highlights how functional evaluations (service quality) and affective responses (attitude and satisfaction) jointly drive customers’ long-term behavioural intentions in the banking sector of developing economies such as Nepal.